Pembelajaran Berbasis Permainan: Upaya Mengurangi Kecemasan Matematika dan Meningkatkan Pemahaman Materi Pecahan - Sopiana, Ari Rofi; Isrok’atun, Isrok’atun; Irawati, Riana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The research was conducted based on the high level of math anxiety among students in mathematics learning, which affects their learning outcomes. Therefore, efforts need to be made to reduce students' math anxiety levels by using game-based learning. This research is quantitative research using a quasi-experimental research method with a nonequivalent control group design. The population in this study was SDN Surian District, Sumedang City, with sampling using purposive sampling of fifth-grade students at SDN Pari and SDN Surian who had high math anxiety. Data analysis techniques included normality tests, nonparametric tests (Mann-Whitney test & Kendall tau test). The results of the study indicate that game-based learning can reduce students' math anxiety levels, and there is a correlation between the reduction in students' math anxiety and their mathematics learning outcomes, particularly in the fractions material. Additionally, there is a difference between the learning outcomes of students using the game-based learning method and those using the conventional learning method.